Comparison of Machine- and Expert-Based Thai Dance Evaluation Methods - Yootthapong Tongpaeng (2019)
© 2018 IEEE. It takes years to learn the Thai dance movements and become an expert. A Thai dance master must train close together with his or her students to transfer tacit knowledge. However, there is a lack of teachers and tools for teaching Thai dance. A Thai dance training tool prototype has to be developed to help the dance students practice dance movement outside the class. The tool is developed to give feedback to Thai dance students on basic dancing movements and to get a better performance based on the feedback. The evaluation process for the Thai dance training tool is taken into consideration. The method is to compare the machine feedback points with the Thai dance expert perspective. The comparison method is using the t-test to get a p-value between two groups and the difference within the groups to provide an evidence of significant value. Therefore, this paper is focusing on comparing machine scores with Thai dance expert scores (scores for each body part and an overall score) with 2 groups of Thai dance movement (Group A B). The result of both groups has shown significant and insignificant values which are irrelevant to the score given by the machine and by the expert. The insignificant result provides the knowledge for improving the evaluation process of the Thai dance training tool.